STUDI KELAYAKAN HABITAT POTENSIAL UNTUK POPULASI KRITIS GAJAH SUMATERA (Elephas maximus sumatranus) - Asvic Helida; Ade Kusuma Sumantri; Ahmad Jabbar; Sela Anggarini (Jurnal Belantara, 2023)
Sumatran elephants are one of the big mammals that are proud of Indonesia, which are classified as endangered and protected species because their population is currently in a critical and threatened condition. On the other hand, the State of Indonesia is an agricultural country, where most of the people are engaged in the agricultural sector which requires land for agriculture and plantations. Population growth and increase have resulted in changes in land and forest functions, so a policy is needed that can accommodate these two interests. Therefore, policies to determine potential and safe habitats for elephant populations need to be implemented. One of these potential habitats is the Gunung Raya Wildlife Reserve, located in Ogan Komering Ulu Selatan Regency, South Sumatra Province. This study aims to determine the feasibility of a potential and safe habitat for the Sumatran elephant population in Ogan Komering Ulu Selatan Regency. The research method is qualitative, namely observation and analysis of vegetation. Observations were made to determine the available habitat components to support elephant life such as springs, minerals, salt, space and shade, while vegetation analysis was carried out to determine the availability of food sources for elephants. The results of research conducted from February to April 2021 show that the Mandoriang Protection Block is a viable, potential and safe habitat for the Sumatran elephant population because it has various types of plants, springs and mineral salts and has a large area of space and shade. can meet the daily movements of the elephants.